2021
DOI: 10.1177/23800844211026608
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wearing Dentures on Dietary Intake, Nutritional Status, and Eating: A Systematic Review

Abstract: Introduction: A key purpose of denture provision is to enable eating, yet the body of evidence pertaining to the impact of dentures on wide-ranging nutritional outcomes has not been systematically reviewed. Objectives: To systematically review published evidence pertaining to the effect of wearing removable dental prosthesis on dietary intake, nutritional status, eating function, and eating related–quality of life (ERQoL). Methods: Eight questions relating to the impact of wearing dentures on nutritional outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…However, no reference was made to support this suggestion. Based on what is known of the functional limitations of dentures on eating function [ 9 ], it is unlikely that those who wear dentures are able to maintain the diet they had when they had natural teeth, and such advice might give those who are new to dentures unrealistic expectations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no reference was made to support this suggestion. Based on what is known of the functional limitations of dentures on eating function [ 9 ], it is unlikely that those who wear dentures are able to maintain the diet they had when they had natural teeth, and such advice might give those who are new to dentures unrealistic expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Provision of dentures improves chewing and biting function but not to the extent of a dentate person [ 9 ]. People that wear dentures report problems with biting, chewing, pain on eating, denture-related stomatitis, sore mouth, reduced flavour perception, embarrassment caused by foods sticking to dentures, and limitations in food choice [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it is costly, takes years to generate results, and may not be generalizable to the treat-ment effectiveness delivered in real-world settings. 49,50 With the digitization of patient care documentation, harnessing electronic health record (EHR) and electronic dental record (EDR) data allows the study of all patients and facilitates longitudinal studies, which are not possible with traditional methods. The potential to link data from disparate data sources such as the EDR and EHR of patients also enables us to study the effect of oral health treatments on their overall health over a longer time.…”
mentioning
confidence: 99%
“…A recent systematic review showed that dentures helped reduce the risk of undernutrition in the edentulous, however, the eating function and eating related quality of life was reduced compared to dentate individuals. Compared to dentate individual's denture wearers had a lower dietary intake, but studies were of poor quality with no application of validated nutritional assessment 48 …”
mentioning
confidence: 99%